2021
DOI: 10.1097/nrl.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changed Serum Brain Biomarkers With Perihematomal Edema and Early Clinical Outcome in Primary ICH Patients

Abstract: Background: Perihematomal edema (PHE) following primary intracranial hemorrhages (ICHs) affects the patient outcome. Also, serum biomarkers such as S100 calcium-binding protein B (S100B) and glial fibrillary acidic protein (GFAP) have been associated with ICHs outcome. We aimed to investigate the association between these biomarkers and PHE in ICH patients. Methods:In this cross-sectional study, patients with primary ICH between January 2020 and August 2020 were evaluated. All participants underwent spiral bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…These immune responses and MMP activity further exacerbate BBB disruption and tissue damage. Previous findings have indicated increased MMP‐9 levels in peripheral blood are associated with hematoma enlargement, poor functional prognosis, and increased PHE growth in patients 102 . Inhibiting MMP‐9 can increase the expression of TJPs and basal protein 40 .…”
Section: The Influence Of Cytokines On Bbbmentioning
confidence: 96%
See 1 more Smart Citation
“…These immune responses and MMP activity further exacerbate BBB disruption and tissue damage. Previous findings have indicated increased MMP‐9 levels in peripheral blood are associated with hematoma enlargement, poor functional prognosis, and increased PHE growth in patients 102 . Inhibiting MMP‐9 can increase the expression of TJPs and basal protein 40 .…”
Section: The Influence Of Cytokines On Bbbmentioning
confidence: 96%
“…Previous findings have indicated increased MMP‐9 levels in peripheral blood are associated with hematoma enlargement, poor functional prognosis, and increased PHE growth in patients. 102 Inhibiting MMP‐9 can increase the expression of TJPs and basal protein. 40 However, some studies have suggested that MMP‐9 activation may not be a contributing factor to the neurological outcomes in hypertension‐induced ICH.…”
Section: The Influence Of Cytokines On Bbbmentioning
confidence: 99%
“…There is also evidence that thrombin can directly disrupt the BBB by increasing the expression of MMPs and AQP4 in vitro and in vivo [ 43 , 44 ]. Although it is a double-edged sword, VEGF may also tend to aggravate the vasogenic edema in the early stage of ICH [ 45 , 46 ]. Additional evidence has indicated that thrombin can promote the release of vascular endothelial growth factor (VEGF) from astrocytes through the PAR-1/p44/42 mitogen-activated protein kinase (MAPK) pathway [ 47 ], suggesting that thrombin can also increase vascular permeability and subsequently promote the evolution of PHE by inducing VEGF overexpression.…”
Section: The Time Phase and Pathophysiology Of Phementioning
confidence: 99%